2007
DOI: 10.2337/dc06-1267
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol Secretion in Patients With Type 2 Diabetes

Abstract: OBJECTIVE -The presence of an enhanced cortisol secretion in patients with type 2 diabetes is debated. In type 2 diabetic subjects, cortisol secretion was found to be associated with the complications and metabolic control of diabetes. We evaluated cortisol secretion in 170 type 2 diabetic subjects and in 71 sex-, age-, and BMI-matched nondiabetic subjects. RESEARCH DESIGN AND METHODS-In all subjects, we evaluated ACTH at 8:00 A.M. in basal conditions and serum cortisol levels at 12:00 P.M. (F24) and at 9:00 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
157
2
13

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(191 citation statements)
references
References 39 publications
14
157
2
13
Order By: Relevance
“…HPA system dysfunction, for example, is associated with major depression, and hypercortisolemia has been demonstrated in the majority of patients with an acute depressive episode (6). Altered cortisol levels have also been observed in diabetes mellitus (7) or arterial hypertension (8), but the significance of these findings is still unclear. In psychophysiology, salivary cortisol sampling is frequently used to unravel the body's response to different stressors (9), and altered cortisol secretion patterns have been observed in posttraumatic stress disorder, burn-out syndrome, work or marital stress, and other conditions (10).…”
Section: Introductionmentioning
confidence: 98%
“…HPA system dysfunction, for example, is associated with major depression, and hypercortisolemia has been demonstrated in the majority of patients with an acute depressive episode (6). Altered cortisol levels have also been observed in diabetes mellitus (7) or arterial hypertension (8), but the significance of these findings is still unclear. In psychophysiology, salivary cortisol sampling is frequently used to unravel the body's response to different stressors (9), and altered cortisol secretion patterns have been observed in posttraumatic stress disorder, burn-out syndrome, work or marital stress, and other conditions (10).…”
Section: Introductionmentioning
confidence: 98%
“…In addition, a common heritable basis between HPA dysfunction and MDD has been suggested based on the finding that non-depressed first-degree relatives of depressed patients exhibit DST abnormalities as a trait [98]. Once established, the HPA axis dysregulation and hypercortisolaemia may further contribute to a hyperglycaemic or poorly controlled diabetic state and has been associated with increased chronic complications of diabetes in adult studies [99].…”
Section: Endocrinological Factorsmentioning
confidence: 99%
“…The current study was designed as an observational study, and whether GV is a cause or consequence of decreased autonomic modulation remains to be elucidated. Nevertheless, studies have shown that glycemic disorders and decreased autonomic modulation are both associated with increased concentrations of inflammatory markers (46,47). As recently demonstrated, there is only a weak correlation between variables of GV and HbA 1c , implying that measurement of HbA 1c alone does not reflect all important aspects of glycemic disorders (16).…”
Section: Resultsmentioning
confidence: 81%